2012
DOI: 10.3390/ijms130911085
|View full text |Cite
|
Sign up to set email alerts
|

Dual Targeting and Retrograde Translocation: Regulators of Plant Nuclear Gene Expression Can Be Sequestered by Plastids

Abstract: Changes in the developmental or metabolic state of plastids can trigger profound changes in the transcript profiles of nuclear genes. Many nuclear transcription factors were shown to be controlled by signals generated in the organelles. In addition to the many different compounds for which an involvement in retrograde signaling is discussed, accumulating evidence suggests a role for proteins in plastid-to-nucleus communication. These proteins might be sequestered in the plastids before they act as transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 96 publications
(119 reference statements)
1
40
0
Order By: Relevance
“…Molecular understanding of the mechanisms targeting HMR to the nucleus and plastids holds promise for gaining novel insight into the mechanisms of nuclear-plastidial communication (Krause and Krupinska, 2009;Krause et al, 2012). In this study, we have showed that HMR can be directly imported into chloroplasts, where it is processed to the mature form starting from Lys-58 (Figs.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Molecular understanding of the mechanisms targeting HMR to the nucleus and plastids holds promise for gaining novel insight into the mechanisms of nuclear-plastidial communication (Krause and Krupinska, 2009;Krause et al, 2012). In this study, we have showed that HMR can be directly imported into chloroplasts, where it is processed to the mature form starting from Lys-58 (Figs.…”
Section: Discussionmentioning
confidence: 79%
“…In this case, the partitioning of the protein between these two compartments is determined by competition and accessibility of the two targeting signals (Karniely and Pines, 2005;Krause and Krupinska, 2009;Krause et al, 2012). For instance, yeast Pir1p contains both a nuclear localization signal and a mitochondrial targeting signal, and its partitioning to these two subcellular compartments is regulated by masking and unmasking of the nuclear localization signal by its binding partner Apn1p (Vongsamphanh et al, 2001).…”
Section: Mechanism Of Dual-targeting Hmr To Plastids and The Nucleusmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, GUN1 contributed to the inhibition of germination by abscisic acid [40]. Similarly, the inhibition of germination by abscisic acid depended on the chloroplast-localized Whirly1 protein [73], which translocates from within the chloroplast to the nucleus [15]. Mutant alleles that activate 3 0 -phosphoadenosine 5 0 -phosphate-dependent plastid-to-nucleus signalling [3] also caused developmental abnormalities in leaves, such as short and round leaves with short petioles, undulating leaves, abnormal leaf vasculature and mesophyll cells [74].…”
Section: Plastid Signals Contribute To Developmentmentioning
confidence: 99%
“…Thus, plastid-to-nucleus signalling broadly affects plant cells by optimizing chloroplast function and helping to coordinate extrachloroplastic processes with chloroplast function. Known plastid signals include hydrogen peroxide, 3 0 -phosphoadenosine 5 0 -phosphate, b-cyclocitral, methylerythritol cyclodiphosphate, thiols and particular proteins [2,3,9,13,15]. Nonetheless, our knowledge of plastid signals and plastid-to-nucleus signalling mechanisms is incomplete.…”
Section: Introductionmentioning
confidence: 99%